Dispositivo expositivo - Marconi Drummond Lage (2011)
From the borderline fields of curatorship, expographics and graphicdesign, this research project proposes studies focusing on aspects andrelationships between the processes of production, circulation andpresentation of the artistic manifestations and the formative elementsof the exhibition chain (artist curator audience). As an object ofstudy, the research is based on a crisscross of original projects(curatorial and graphic) developed at the Pampulha Art Museum (MAP -Belo Horizonte, Brazil) between 2006 and 2010. Artistic practices andmanifestations directly connected to the art dematerializationexperiments developed by conceptual artists of the 1960s areaddressed within the discussions of these original projects.Contemporary counterpoints are presented. Adjacent to thedissertation text there is another text, both documental andiconographic: ten exhibit catalogues drawn for MAP. The objective ofthe research is to speculate on the curatorial practice unfolded in twodifferent supports: the graphic organization of the exhibit space and theexpographic space of the publication.